2020
DOI: 10.3390/su12135229
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Peer-to-Peer, Two-Sided Digital Marketplaces: Pricing Lessons from Airbnb in Barcelona

Abstract: Peer-to-peer, two-sided digital marketplaces are reshaping the way in which consumers exchange products and interact with brand value propositions, particularly in the travel and tourism industry. Within the dynamics of these marketplaces, pricing approaches are of the utmost importance; yet, in contrast to conventional digital marketplaces, prices are set by non-professional vendors who are also consumers. We contribute to research on the topic by examining pricing within a single peer-to-peer, two-sided mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…Hence, we suggest that the platform firm should make managerial decisions to enlarge the differentiation in positioning for the two types of hosts and segment tourists. This suggestion is consistent with a recent stream of research [27,39].…”
Section: Practical Implicationssupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, we suggest that the platform firm should make managerial decisions to enlarge the differentiation in positioning for the two types of hosts and segment tourists. This suggestion is consistent with a recent stream of research [27,39].…”
Section: Practical Implicationssupporting
confidence: 93%
“…The role of price is frequently debated in economics [21,25,26]. Particularly in the field of hospitality and airline transportation management, price is the most important criteria across hospitality choices [22,27]. The importance attributed to pricing decisions mainly arises from the intrinsic nature of the tourism product as a perishable and unstorable service [26], considering the near-zero marginal cost [28].…”
Section: Price Interactions Between Professional and Nonprofessional Decision Makers And Market Outcomementioning
confidence: 99%
“…Questions have been raised about whether Airbnb’s supply distribution is related to proximity to cities’ tourist attractions but also transport and educational infrastructures (Morales-Pérez et al, 2020) or to other socioeconomic factors, such as a young population (Dudás et al, 2017), a large proportion of single-person households (Ki and Lee, 2019) or even the attractiveness of lifestyle consumption (neo-bohemia) (Ioannides et al, 2018). In fact, studies such as those by Benítez-Aurioles (2018), Gibbs et al (2018), Li et al (2019) and Lladós-Masllorens et al (2020), have established a close link between the location of Airbnb’s supply and the attractiveness and perceived value of these places for potential tourists. More recently, Lagonigro et al (2020) stated that the main factors explaining the spatial development of Airbnb listings have mainly been socioeconomic: residents’ family income and education level, and dwelling sizes in these spaces.…”
Section: Literaturementioning
confidence: 99%
“…Their results showed "worrying indicators" regarding the economic and social sustainability of the city's tourist model. In addition, Lladós-Masllorens et al (2020) studied the pricing strategy of listings in Airbnb in Barcelona and found that a systematic interaction of valence and volume of online reviews can produce a crucial impact on the listings' pricing. Other authors have found, through Airbnb reviews in Barcelona, that the location of the accommodation strongly influences the online travel review (OTR) narrative, which may affect the destination's image, tourist satisfaction, and loyalty (Marine-Roig, 2021).…”
Section: Barcelona As a Case Of Studymentioning
confidence: 99%